Relationship of Perceived Social Support With Sleep Quality and Mental Health in the Elderly Referred to Health Centers in Tehran, Iran - Aazam Damerchi lou; Mohtasham Ghaffari; Maasomeh Sadeghipour Roudsari; Sakineh Rakhshanderou (University of Social Welfare & Rehabilitation Sciences, 2024)
Objectives The increase in the aged population, associated with various diseases and problems that threaten physical and mental health, as well as the social and economic developments and changes in individual and family lifestyles, have caused inappropriate emotional responses such as stress, anxiety and depression in the elderly in Iran. The present study aims to determine the relationship of perceived social support with sleep quality and mental health in elderly people referred to health centers in Tehran, Iran.  Methods & Materials This is a descriptive-analytical study with a cross-sectional design that was conducted on 420 elderly people referred to health centers affiliated to Shahid Beheshti University of Medical Sciences in Tehran in 2021, who were selected by a multi-stage random sampling method. A demographic form, the pittsburgh sleep quality index (PSQI), the depression anxiety stress scale-21 (DASS-21), and the multidimensional scale of perceived social support (MSPSS) were used to collect information. Data analysis was done using Pearson's correlation test and descriptive statistics (frequency, percentage, mean, standard deviation, skewness, and kurtosis) in SPSS software version 25 and path analysis in EQS software, version 6.4.  Results The findings indicated that 54.5% of the elderly had depression, 64% had anxiety, 49.3% had stress, and 91.4% had sleep disorders. A negative and significant correlation was found between perceived social support and mental health components (depression, anxiety, and stress) in the elderly (P<0.001). and also between perceived social support and sleep quality (P<0.001).  Conclusion Considering the positive relationship of perceived social support with mental health and sleep quality of the elderly in Tehran, there is a need to pay more attention to their perceived social support.